HOW TO DEVELOP STRATEGIC LEADERSHIP IN HIGHER EDUCATION INSTITUTION? - Nur Hidayah (2015)
In a turbulent environment and difficult to predict, effective strategic leadership is the foundation of success in a strategic management process. The aim of this research was to analyze the dimensions of strategic leadership and how the dimensions influence of the strategic leadership. The research method used was a survey. The sample comprised 67 respondents; Chairman of the Study Programs of graduate (Strata 1) and Postgraduate (Strata 2) of Economics and Management College in Jakarta. Data were analyzed using Partial Least Square (PLS). The result shows that from the three dimensions of strategic leadership, the dimension which gives the biggest contribution to strategic leadership is to be a strategic expert (strategist), then is as change agent, and the last is as a visionary leader. The implication of this results is to improve the effective strategic leadership, a leader have to be a strategic expert, then to be change agent and should be able to create clear and relevant visions and mission of the organization